RANCANGBANGUN SISTEM PEMANTAU PENGANGKUTAN ZAT RADIOAKTIF MENGGUNAKAN SMS TERSANDI - , ADI ABIMANYU ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Safety and security aspects of radioactive substances from the sender to the receiver are important and should be assured. This research proposes a monitoring system, which integrates surveymeter, GPS, and wireless communication using encrypted SMS. The SMS is encrypted using the proposed Hybrid algorithm, which is a combination between Vigenere and Vernam algorithm. Thus, the proposed prototype can monitor the dose rate (radiation rate) and vehicle position that carries radioactive substances, and support the communication of encrypted information that can be monitored remotely in realtime fashion by supervisor in the control room. Test results show that radiation monitor module operates within stability counting value (chi-square) range of 34.76467.50